Combined pyrolysis and sulphided NiMo/Al2O3 catalysed hydroprocessing in a multistage strategy for the production of biofuels from milk processing waste. (1st July 2021) - McIntosh, Shane; Nabi, Md Nurun; Moghaddam, Lalehvash; Brooks, Peter; Ghandehari, Parya Samadi; Erler, Dirk
Highlights: A method for obtaining biofuels from milk processing waste is demonstrated. Low temperature slow pyrolysis maximised bio-oil yields (57.7%). Crude bio-oil characterisation asserts potential direct fuel applications. Upgrading via catalytic hydroprocessing produced fuels with diesel qualities. Abstract: Pyrolytic bio-oils derived from renewable organic wastes are credible second-generation biofuels. In crude form, bio-oils are inherently complex mixtures that largely limit their direct application as fuels and integration into existing petroleum infrastructure, without additional upgrading. Herein, we report on low-oxygenated biofuel production from milk processing sludge using a multistage process configuration. In the first stage, bio-oil yields were maximised (57.7%) under slow pyrolysis conditions at 450 °C. Bio-oils were enriched in aliphatic hydrocarbons (19–22% alkanes), (11–14% alkenes) and alkyl nitriles (57–63%), while aromatics remained low at <2%. A relatively low bio-oil O/C molar ratio (0.08 to 0.1) and a correspondingly high HHV (40.8–41.8 MJ/kg) display possible fuel applications. Increasing pyrolysis temperatures (>450 °C) was not beneficial to bio-oil yields, reduced hydrocarbon contents and increased heteroatoms (O, S, N). In the second stage, sulphided Ni-Mo/Al2 O3 catalysed hydroprocessing and distillation upgrading of bio-oils generated 100% C8 -C22 saturated alkane distillates. With regard to fuel properties, oxygenation (0.26–0.89%), viscosities (4–6 mm 2 /s) and densities (ca.0.82 g/cm 3 ) were comparable to standard diesel fuels. Resultant HHV (46.24 MJ/kg) and cetane index (69) of distillates produced from 450 °C bio-oils far exceeded those of diesel fuel standards, demonstrating direct fuel application and petroleum fuel compatibility.